Beyond (the cave of) pitch/loudness-equalization: A Commentary on Reymore (2021) - Siedenburg, Kai (Empirical Musicology Review, 2023)
Traditional approaches in timbre research have often equalized sounds according to pitch, loudness, duration in order to study timbral differences across instruments. In a compact case study of the semantic qualities of the oboe and French horn, Reymore (2021) takes a different approach and considers timbral differences within musical instruments, which arise due to the covariation of timbre with the musical parameters of fundamental frequency (pitch) and playing effort (dynamic level). The study constitutes a timely contribution to a growing body of work on the covariation between timbre, pitch, and loudness. After providing a background and summary of important aspects of the target article, I elaborate on results from a recent complementary study that analyzed acoustical signal properties regarding that matter. Finally, I address three important issues in this context that appear to be worthy of future research.